Mott-Hubbard versus charge-transfer behavior in LaSrMnO4 studied via optical conductivity - Gössling, Alexander; Haverkort, Maurits W. (Arxiv, 2008)
Using spectroscopic ellipsometry, we study the optical conductivity sigma(omega) of insulating LaSrMnO4 in the energy range of 0.75-5.8 eV from 15 to 330 K. The layered structure gives rise to a pronounced anisotropy. A multipeak structure is observed in sigma_1^a(omega) (2, 3.5, 4.5, 4.9, and 5.5 eV), while only one peak is present at 5.6 eV in sigma_1^c(omega). We employ a local multiplet calculation and obtain (i) an excellent description of the optical data, (ii) a detailed peak assignment in terms of the multiplet splitting of Mott-Hubbard and charge-transfer absorption bands, and (iii) effective parameters of the electronic structure, e.g., the on-site Coulomb repulsion U_eff=2.2 eV, the in-plane charge-transfer energy Delta_a=4.5 eV, and the crystal-field parameters for the d^4 configuration (10 Dq=1.2 eV, Delta_eg=1.4 eV, and Delta_t2g=0.2 eV). The spectral weight of the lowest absorption feature (at 1-2 eV) changes by a factor of 2 as a function of temperature, which can be attributed to the change of the nearest-neighbor spin-spin correlation function across the Neel temperature. Interpreting LaSrMnO4 effectively as a Mott-Hubbard insulator naturally explains this strong temperature dependence, the relative weight of the different absorption peaks, and the pronounced anisotropy. By means of transmittance measurements, we determine the onset of the optical gap Delta^a_opt=0.4-0.45 eV at 15 K and 0.1-0.2 eV at 300 K. Our data show that the crystal-field splitting is too large to explain the anomalous temperature dependence of the c-axis lattice parameter by thermal occupation of excited crystal-field levels. Alternatively, we propose that a thermal population of the upper Hubbard band gives rise to the shrinkage of the c-axis lattice parameter.